Socrates dialogue as a technique in group counseling to improve communication skills - Wahyudiansah, Muhammad Nafis; Mufidah, Elia Firda; Hartanti, Jahju (Universitas Islam Negeri Raden Intan Lampung, 2022)
Every student should have the ability to organize ideas rationally and methodically, transform them into understandable language, and speak them fluently and clearly. The purpose of this research was to investigate the efficacy of employing the Socratic discussion technique in group counseling to improve interpersonal communication. This is a quasi-experimental study with a single-group design. The sample size was seven participants, and data was collected using a communication skills questionnaire and evaluated using the T-test. The analysis revealed a Sig (2-tailed) paired samples test result of 0.000 where the result was <0.05, indicating that group counseling services using the technique of Socratic dialogue have an effective impact on developing students' communication skills.